Islamic Educational Values in the Circumcision Tradition of the Lampung Saibatin Indigenous Community in Kunyayan Village, Wonosobo District, Tanggamus Regency - Tiara Mutia Putri; Saiful Bahri; Era Octafiona; Grace Temilolu Ikenna (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2025)
The circumcision tradition in the Saibatin Lampung indigenous community in Kunyayan Village, Wonosobo District, Tanggamus Regency, is not merely a religious ritual but also serves as a means of character education that integrates Islamic educational values with local culture. This study aims to examine the Islamic educational values embedded in this circumcision tradition, through the stages involving the ngarak maju procession, butammat, pemacakhan, and the circumcision itself. Using a qualitative approach with a phenomenological research design, data were obtained through participatory observation, in-depth interviews, and documentation from community leaders, religious figures, and community members directly involved. The findings indicate that this circumcision tradition teaches values of Aqidah (faith), Ibadah (devotion), Akhlak (morality), and social responsibility, which are reflected in the process and active participation of the community. Additionally, the values of Musyawarah (consultation), Ukhuwah Islamiyah (Islamic brotherhood), and Piil Pesenggiri (a local cultural value) are also internalized in the social practices during the procession. The study also notes the modern adaptations accepted by the community, such as the use of professional medical personnel and digital technology, without diminishing the cultural essence and the Islamic values inherent in the ritual. Thus, this circumcision tradition functions as a form of non-formal, culture-based education that teaches character through symbols, actions, and direct community involvement.